Congenital heart disease research landscape in the Arab world: a 25-year bibliometric review - Bitar, Fouad; Arabi, Mariam; Bulbul, Ziad; Nemer, Georges; Jassar, Yehya; Bitar, Fadi F.; Abdul Sater, Zahi (Frontiers in Cardiovascular Medicine, 2024)
Background While research on congenital heart disease has been extensively conducted worldwide, comprehensive studies from developing countries and the Arab world remain scarce. Aim This study aims to perform a bibliometric review of research on congenital heart disease in the Arab world from 1997 to 2022. Methods We analyzed data from the Web of Science, encompassing various aspects such as topics, countries, research output, citations, authors, collaborations, and affiliations. This comprehensive science mapping analysis was done using the R statistical software's Bibliometrix Package. Results The research output from Arab countries over the 25 years showed an average annual growth rate of 11.5%. However, Arab countries exhibited lower research productivity than the United States and Europe, with a 24-fold difference. There was substantial variation in research output among 22 Arab countries, with five countries contributing to 78% of the total publications. Most of the published research was clinical, with limited innovative contributions and a preference for regional journals. High-income Arab countries displayed higher research productivity and citation rates than their low-income developing counterparts. Despite being categorized as upper-middle-income, post-conflict countries exhibited low research productivity. About one-quarter of the published articles (26%) resulted from collaborative efforts among multiple countries, with the United States being the most frequent collaborator. Enhanced research productivity and impact output were strongly associated with increased international cooperation. Conclusion Research productivity in the Arab region closely correlates with a country's GDP. Success hinges on governmental support, funding, international collaboration, and a clear research vision. These findings offer valuable insights for policymakers, educational institutions, and governments to strengthen research programs and nurture a research culture.